Association of red blood cell count, hemoglobin concentration, and inflammatory indices with cognitive impairment severity in Alzheimer’s disease - Yali Zheng; Yongxiang Yu; Linli Gao; Ming Yu; Lijun Jiang; Quanfeng Zhu (Scientific Reports)
Abstract Some studies have found that patients with Alzheimer’s disease (AD) have changes in levels of red blood cell (RBC) and hemoglobin (HB), and some inflammatory indexes are increased. However, the results of relevant studies are not uniform. The aim of this study is to investigate the changes of RBC, HB, and commonly used inflammatory indexes in patients with AD and their correlation with the severity of cognitive impairment. A total of 225 subjects with AD and 2000 healthy controls were included. Dementia severity was evaluated by Mini-Mental State Examination (MMSE). The RBC count and HB concentration of subjects were detected, and inflammatory indexes including neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) and monocyte/lymphocyte ratio (MLR), systemic immune inflammation index (SII), systemic inflammation response index (SIRI), and pan-immune-inflammation value (PIV) were calculated. RBC count, HB concentration, NLR, PLR, MLR were independent influencing factors for AD. RBC count and HB concentration are significantly associated with the severity of cognitive impairment in AD patients. RBC count has a significant effect on the severity of cognitive impairment without considering the education level, but their effects on the severity of cognitive impairment are no longer significant when the education level is considered. The RBC count and HB concentration of AD patients are decreased, and are correlated with the severity of cognitive impairment. In addition, some inflammatory indexes are associated with the risk of AD.